Effects of adding trace elements on rice straw anaerobic mono-digestion: Focus on changes in microbial communities using high-throughput sequencing. (September 2017) - Cai, Yafan; Hua, Binbin; Gao, Lijuan; Hu, Yuegao; Yuan, Xufeng; Cui, Zongjun; Zhu, Wanbin; Wang, Xiaofen
Graphical abstract: Highlights: The effects of trace elements on rice straw anaerobic digestion were evaluated. Adding Co and Ni did not improve reactor performance. Fe, Mn, Mo, Se accelerated the degradation of VFAs and methane generation. The change of composition and diversity of microorganism affected methane yield. Abstract: Although trace elements are known to aid anaerobic digestion, their mechanism of action is still unclear. High-throughput sequencing was used to reveal the mechanism by which adding trace elements affects microbial communities and their action. The results showed that the highest methane yields, with addition of Fe, Mo, Se and Mn were 289.2, 289.6, 285.3, 293.0 mL/g volatile solids (VS), respectively. The addition of Fe, Mo, Se and Mn significantly ( P < 0.05) reduced the level of volatile fatty acids (VFAs). The dominant bacteria and archaea were Bacteroidetes and Methanosaeta, respectively. Compared with the proportion of Methanosaeta in the control group, treatment with added trace elements increased Methanosaeta by as much as 12.4%. Microbial community analysis indicated that adding trace elements changed the composition and diversity of archaea and bacteria. Methane yield was positively correlated with bacterial diversity and negatively correlated with archaeal diversity for most treatments.